Synthesis of Porous Covalent Quinazoline Networks (CQNs) and Their Gas Sorption Properties. (13th December 2018) - Buyukcakir, Onur; Yuksel, Recep; Jiang, Yi; Lee, Sun Hwa; Seong, Won Kyung; Chen, Xiong; Ruoff, Rodney S.
Abstract: The development of different classes of porous polymers by linking organic molecules using new chemistries still remains a great challenge. Herein, we introduce for the first time the synthesis of covalent quinazoline networks (CQNs) using an ionothermal synthesis protocol. Zinc chloride (ZnCl2 ) was used as the solvent and catalyst for the condensation of aromatic ortho ‐aminonitriles to produce tricycloquinazoline linkages. The resulting CQNs show a high porosity with a surface area up to 1870 m 2 g −1 . Varying the temperature and the amount of catalyst enables us to control the surface area as well as the pore size distribution of the CQNs. Furthermore, their high nitrogen content and significant microporosity make them a promising CO2 adsorbent with a CO2 uptake capacity of 7.16 mmol g −1 (31.5 wt %) at 273 K and 1 bar. Because of their exceptional CO2 sorption properties, they are promising candidates as an adsorbent for the selective capture of CO2 from flue gas.